2005
DOI: 10.1001/archsurg.140.11.1074
|View full text |Cite
|
Sign up to set email alerts
|

Women Authors of Surgical Research

Abstract: The number of women authors in the surgical literature has increased during the past 20 years. Design: Randomly selected issues of odd-year journals in Archives of Surgery and Annals of Surgery from January 1, 1985, to December 31, 2003, were reviewed. We determined the gender of each author and reported trends in the occurrence of women authors over time. Results: The percentage of women authors has increased over time and parallels the percentage of women faculty in academic surgery positions. A much higher … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

5
40
1
1

Year Published

2009
2009
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 53 publications
(47 citation statements)
references
References 19 publications
5
40
1
1
Order By: Relevance
“…Authorship patterns may indicate the participation of women in academic surgery (Kurichi et al, 2005). The gender gap in authorship still exists as evidenced by our observation and others studies (Kurichi et al, 2005;Taira et al, 2008).…”
Section: Discussionsupporting
confidence: 64%
See 1 more Smart Citation
“…Authorship patterns may indicate the participation of women in academic surgery (Kurichi et al, 2005). The gender gap in authorship still exists as evidenced by our observation and others studies (Kurichi et al, 2005;Taira et al, 2008).…”
Section: Discussionsupporting
confidence: 64%
“…If the first-author gender was unclear, we did an internet search for the author by name and institution, and other strategies as described by Kurichi et al (2005). Industrial support for only drugs or devices was not recognised as a funding source.…”
Section: Methodsmentioning
confidence: 99%
“…8 There are a handful of articles that examine gender trends in the fields of general surgery, otolaryngology, orthopedic surgery, anesthesiology, dermatology, and dentistry, showing that there was often, but not always, an increase in women authors publishing during the past decade. 7,[9][10][11][12][13][14][15] These studies also found that gender trends in authorship varied between subspecialties. For example, orthopedic surgery did not have the same increase in women authors compared with other fields.…”
mentioning
confidence: 73%
“…Gender differences in scholarly activity are well-documented across the spectrum of scientific disciplines (5)(6)(7)(8)(9). The trend appears to also hold true in academic radiation oncology, as evidenced by the significantly lower mean and quartile h-index values for female radiation oncologists overall compared with their male counterparts (Table 1) (10).…”
Section: Women In Radiation Oncologymentioning
confidence: 94%